Autoimmune and autoinflammatory manifestations in inborn errors of immunity. Issue 6 (21st December 2022) - Kačar, Mark; Markelj, Gašper; Avčin, Tadej
Abstract : Purpose of review: Autoimmune and inflammatory complications have been shown to arise in all age groups and across the spectrum of inborn errors of immunity (IEI). This review aims to highlight recent ground-breaking research and its impact on our understanding of IEI. Recent findings: Three registry-based studies of unprecedented size revealed the high prevalence of autoimmune, inflammatory and malignant complications in IEI. Two novel IEI were discovered: an autoinflammatory relopathy, cleavage-resistant RIPK1-induced autoinflammatory syndrome, as well as an inheritable phenocopy of PD-1 blockade-associated complication (as seen in cancer therapy) manifesting with multiorgan autoimmunity and Mycobacterium tuberculosis infection. A study examining patients with partial RAG deficiency pinpointed the specific defects leading to the failure of central and peripheral tolerance resulting in wide-ranging autoimmunity. A novel variant of Immunodeficiency Polyendocrinopathy Enteropathy X-linked syndrome was described, associated with preferential expression of a FOXP3 isoform lacking exon 2, linking exon-specific functions and the phenotypes corresponding to their absence. Lastly, we touch on recent findings pertaining actinopathies, the prototypical IEI with autoimmune, inflammatory and atopic complications. Summary: Dysregulated immunity has been associated with IEI since their discovery. Recently, large concerted efforts have shown how common these complications actually are while providing insight into normal and dysregulated molecular mechanisms, as well as describing novel diseases.